EFEKTIFITAS PEMBERIAN REBUSAN DAUN ALPUKAT TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI DI PUSKESMAS SIWALANKERTO SURABAYA - Tyas Solit Naomiyah; Dya Sustrami; Sukma Ayu C Kirana (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2019)
Background: Hypertension is the highest cause of death in Indonesia. Non-pharmacological therapy that could reduce blood pressure was decoction of avocado leaves. This study aims to determine effectiveness decoction of avocado leaves to blood pressure of hypertensive patients in Siwalankerto Health Center Surabaya. Methods: This research used Quasy experimental one groups pre test-posttest with control design with a quantitative approach. Sampling techniques used was probability sampling with simple random sampling which obtained sample of 30 respondents aged 26-45 years old.15 respondents in the avocado leaves decoction intervention groups and 15 respondents in the control groups. Data analysis was carried out with the help of computer programs by using Paired T-Test. Result: result of the Paired T-Test of systolic and dyastolic blood pressure obtained p = 0,000 with a significance level (p<0,05), meaning that there was an influence between before and after giving treatment of avocado leaves decoction to blood pressure of hypertensive patients in Siwalankerto Health Center Surabaya. Conclusion: The research implication showed that complementary therapies provided by nurses could be a motivation to achieve the goals of hypertension self care.